Stalked barnacle (Pollicipes pollicipes) harvesting in the Berlengas Nature Reserve, Portugal: temporal variation and validation of logbook data - Jacinto, D. (2012)
Stalked barnacle (Pollicipes pollicipes) exploitation at the Berlengas Nature Reserve, Portugal, by professional harvesters has been subject to specific regulation since 2000. The only available information on barnacle exploitation there comes from catch reports (log- books) provided by the harvesters. We evaluated the quality of the logbook information, described the temporal patterns of P. pollicipes fishing effort from 2000 to 2006 based on the logbook data, and modelled the daily fishing effort in relation to variability in oceanographic conditions. Results suggest different levels of reliability for the information contained in the logbooks: (i) information on the date of harvest seems to be reliable because 83% of the observed harvest dates were also declared; (ii) information on the quantity harvested shows a large discrepancy (mean 1⁄4 31.8%) between declared and observed amounts, but we believe it can be used to analyse temporal patterns of exploitation, because there was no systematic bias (under- and overreporting was to the same extent). The total quantity of barnacles harvested between 2000 and 2006 ($16 t year21) was closely related to the effort applied. Daily harvesting effort was considered a function of two predictive variables (significant wave height and tidal range) and of their interaction. Neither the harvesting activity nor the resource itself seems to be at risk of collapse if such levels of pressure are maintained, but efforts should be made to increase surveillance and monitoring within the marine protected area.